Recontextualizing Web-Based Sources in Report Writing: Exploring Students’ Meaning-Making Practices - Fahrurrozi, Muhammad; Sofiani, Evi Maulidah; Sofiana, Eva Maulidah (STIT Buntet Pesantren Cirebon, 2025)
This qualitative study examines how third-semester EFL students at UIN Siber Syekh Nurjati Cirebon engage with web-based sources in academic report writing. Drawing on theories of intertextuality, genre-based pedagogy, and digital literacy, the research investigates students’ strategies in selecting, interpreting, and integrating online information when composing a report on Cirebon wedding traditions. Data from student texts and semi-structured interviews were analysed thematically using Braun and Clarke’s framework. Findings show that students employed targeted keyword searches and demonstrated awareness of genre structure, but tended to rely on top-ranked institutional sources and simplified conflicting information. While they displayed emerging control over paraphrasing and citation, their critical evaluation of digital content, especially in relation to algorithmic bias and underrepresented perspectives, remained limited. The study underscores the need to expand writing instruction beyond functional skills to include ethical source use, algorithmic awareness, and critical authorship, especially in contexts where AI-assisted tools are increasingly accessible. It recommends further research into how intertextual practices evolve across genres, disciplines, and technological environments. This study positions EFL learners as developing digital authors who require pedagogical support to write with critical awareness in a digitally saturated world.